(In)Visibility and recognition: Australian policy responses to 'domestic violence'. (September 2019) - Seymour, Kate
This article explores representations of gender and violence in Australia's National Plan to Reduce Violence Against Women and Children. The Plan's neglect of violence in the context of LGB relationships is discussed as indicative of the Plan's implicit heteronormativity and its uncritical reliance on dominant discourses of gender and violence. In its failure to engage with the diverse complexities of gender and violence, I argue that the Plan perpetuates the exclusion of certain bodies, identities and experiences, such that rights to protection and safety are reserved for some and not others.